Competition increasingly dominates the responsiveness of juvenile beech and spruce to elevated CO₂ and/or O₃ concentrations throughout two subsequent growing seasons - Kozovits, A.R; Matyssek, R; Blaschke, H; Gottlein, A; Grams, T.E.E (Global change biology, 2005)
Saplings of Fagus sylvatica and Picea abies were grown in mono‐ and mixed cultures in a 2‐year phytotron study under all four combinations of ambient and elevated ozone (O3) and carbon dioxide (CO2) concentrations. The hypotheses tested were (1) that the competitiveness of beech rather than spruce is negatively affected by the exposure to enhanced O3 concentrations, (2) spruce benefits from the increase of resource availability (elevated CO2) in the mixed culture and (3) that the responsiveness of plants to CO2 and O3 depends on the type of competition (i.e. intra vs. interspecific). Beech displayed a competitive disadvantage when growing in mixture with spruce: after two growing seasons under interspecific competition, beech showed significant reductions in leaf gas exchange, biomass development and crown volume as compared with beech plants growing in monoculture. In competition with spruce, beech appeared to be nitrogen (N)‐limited, whereas spruce tended to benefit in terms of its plant N status. The responsiveness of the juvenile trees to the atmospheric treatments differed between species and was dominated by the type of competition: spruce growth benefited from elevated CO2 concentrations, while beech growth suffered from the enhanced O3 regime. In general, interspecific competition enhanced these atmospheric treatment effects, supporting our hypotheses. Significant differences in root : shoot biomass ratio between the type of competition under both elevated O3 and CO2 were not caused by readjustments of biomass partitioning, but were dependent on tree size. Our study stresses that competition is an important factor driving plant development, and suggests that the knowledge about responses of plants to elevated CO2 and/or O3, acquired from plants growing in monoculture, may not be transferred to plants grown under interspecific competition as typically found in the field.